2018
DOI: 10.3892/or.2018.6640
|View full text |Cite
|
Sign up to set email alerts
|

miR‑197 promotes the invasion and migration of colorectal cancer by targeting insulin‑like growth factor‑binding protein�3

Abstract: The incidence and mortality of colorectal cancer (CRC) have been rising rapidly in China. A number of miRNAs have been confirmed to be involved in diverse biological processes of CRC. However, whether miR‑197 plays a role in migration and invasion of CRC has never been explored. In the present study Transwell chambers were used in in vitro migration and invasion assays. Dual-luciferase reporter assay was employed to confirm the target of miR‑197. RT‑PCR and IHC staining were performed to quantify miR‑197 and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
(38 reference statements)
1
8
1
Order By: Relevance
“…Of note, contrary to our research, Zhou et al confirmed that decreased expression of IGFBP3 promoted tumor metastasis in CRC [ 34 ]. Another study indicated that silencing IGFBP3 in two human CRC cell lines, SW480 and Caco2, could reduce the proliferation, colony formation, and migration.…”
Section: Discussioncontrasting
confidence: 99%
“…Of note, contrary to our research, Zhou et al confirmed that decreased expression of IGFBP3 promoted tumor metastasis in CRC [ 34 ]. Another study indicated that silencing IGFBP3 in two human CRC cell lines, SW480 and Caco2, could reduce the proliferation, colony formation, and migration.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, in this study, we identified a ten-microRNA signature to better predict the prognosis of COAD patients. Among those selected microRNAs, seven of them (hsa-miR-32, hsa-miR-197, hsa-miR-210, hsa-miR-3189, hsa-miR-3917, hsa-miR-4999, and hsa-miR-6854) were previous reported to have critical roles in colorectal carcinoma [13][14][15][16]. Three of them (hsa-miR-3189, hsa-miR-3917 and hsa-miR-6854) appear to be protective factors for colon cancer consistent with previous study and four of them (hsa-miR-32, hsa-miR-197, hsa-miR-210 and hsa-miR-4999) display to be risky factors for colon cancer also consistent with previous study.…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancer cells, the oncogenic protein IGF2BP2 has a functional interaction with miR-195 through which it regulates RAF1 expression and participates in the carcinogenic process (Ye S. et al, 2016). Meanwhile, miR-197 can inhibit the expression of IGFBP3 through binding with its 3 -UTR, hence enhancing cell migratory potential and invasion of colorectal cancer cells (Zhou et al, 2018). Supplementary Table 1 reviews the results of studies that displayed the role of IGF-associated miRNAs in the neoplastic conditions.…”
Section: Igf-associated Mirnas In Human Disordersmentioning
confidence: 99%